Neuropsychological profile linked to low dopamine: in Alzheimer's disease, major depression, and Parkinson's disease. Issue 10 (October 1990) - Wolfe, N; Katz, D I; Albert, M L; Almozlino, A; Durso, R; Smith, M C; Volicer, L
Abstract : A distinct pattern of neuropsychological deficits was associated with low homovanillic acid (HVA) in the cerebrospinal fluid of 21 patients with: Alzheimer's disease (9), Parkinson's disease (8) and major depressive disorders (4). Regardless of clinical diagnosis, patients with low HVA were slower on a test of efficiency of processing timed information, and showed greater benefit from semantic structure on a verbal fluency task than patients with high HVA. However, low HVA subjects were not significantly impaired on confrontation naming (Boston Naming Test). Across three diagnostic groups, patients with lower HVA also tended to have more extrapyramidal motor signs and were significantly more depressed. These results demonstrate a significant relationship between specific neuro-behavioural deficits and dopaminergic activity which cuts across traditional diagnostic categories.